Rassegroepe se evaluering van kriteria by motovoertuigaankope - P. J. Du Plessis (South African Journal of Business Management, 1987)
– The objective of this study was to determine whether differences and/or similarities exist in the relative importance of evaluation criteria between the various race groups in South Africa when purchasing a motor vehicle. The sample consisted of 577 whites, 114 coloureds, 102 Asians and 109 blacks mainly from metropolitan areas. Variance analysis was applied to establish that there were 52 significant differences out of a total of 65 evaluation criteria with respect to the various race groups. Results showed that the biggest significant differences occurred between whites and blacks (66% of the evaluation criteria) and between whites and Asians (43% of the evaluation criteria).
Keywords: 650